SISTEM PENGENDALIAN MANAJEMEN DALAM MENINGKATKAN MUTU PERGURUAN TINGGI - Elfrianto Elfrianto (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Management control system in an organization or institution is needed, especially for a nation or country is to fix itself, towards improving the quality, especially in college. Because it is a place where someone forged, educated, guided and directed to be able to be a human beings who have ideals, capable of realizing the ideals of both the ideals of itself, family, nation and country.The purpose of the management control system design to effort is to get the reliability and integrity of information, compliance with policies, plans, procedures, rules and regulations, protecting company property, efficient result and economic activities. Knowledge of management should be owned by everyone for himself, or another persons or groups, in this hope to manage themselves and to manage the subordinates to achieve goals.